Financial Distress as a Moderating Effect of Management Turnover, KAP Size, and Audit Fees on Auditor Switching in the Indonesian Stock Exchange - Puspita Isnu Fianti; Achmad Badjuri (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2023)
This research aims to examine the impact of replacing the KAP management scale and audit costs on auditor turnover, considering the moderating variable of financial distress. The relationship between these various variables can be explained by agency theory, which describes the agency relationship when one or more parties work together or enter into agreements with others as agents to provide specific services. This study also uses the deep pocket theory. The population studied consists of 260 samples, which are companies listed on the Indonesian Stock Exchange (BEI) selected through purposive sampling. The research method used to analyze the data is logistic regression and moderating regression. The experimental results show that the dimensions of KAP have a significant negative impact on auditor turnover, while changes in management and audit costs do not influence auditor turnover. Findings from multiple regression analysis (MRA) indicate that financial distress strengthens the relationship between management changes, dimensions of KAP, audit costs, and auditor turnover.